(3ebGdI aj GdbhS hGdgGdIs - (3GHf GdgjKe , eMeO Hf GdMSf Hf GdgjKe, CHh Ydj HWdjehS GdKGfj,J (B430 (3g` s ((3eMeO Hf GdWGgQ Hf GdMHjH s)
(3ChdgG (B:s
(3cd eYfi jHMK Yf MbjbI aEfeG jHMK YfgG HGdfMh GdeJLGfS dfhYg aEf cGf HSjWG ajfXQ HSjWG s
(3BNQgG (B:s
(3hjMJed GdCeQ GdWHjYi hjchf eWGHbkG hJeJ ebGdI GdMSf Hf GdMSf Hf GdgjKe ai GdbhS hGdgGdg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B83 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B225s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs